Penerjemahan Resep Masakan dari Berbagai Budaya ke dalam Bahasa Indonesia - Barathayomi, Wieka (Jurnal Penerjemahan, 2022)
This article presents useful information for translating cooking recipes from English into Indonesian in terms of the characteristics of linguistic and cultural aspects in cooking recipes, the challenges that cause translationdifficulties, and the strategies to overcome challenges in translation. This article focuses on student translators. Student translators have to translate many kinds of texts, one of them is cooking recipes (procedure text). In order to translate the texts, an understanding of the language structure of source text and target text and the culture aspects are crucial. The challenges that cause translation errors in student translators will be examined through the perspective of the author's teaching experience and a review of the appropriate literature, and then, some tips and strategies will be offered to solve problems in translation. Keywords: English-Indonesian translation, teaching translation, language teaching, cooking recipe.